Some Relevant Terms in the Study of Vietnamese Serial Verb Constructions - Đông, Lâm Quang (VNU Journal of Science: Social Sciences and Humanities; Vol 28 No 5E, 2012)
Abstract . Our previous article on multi-verb sentences [1] referred to such concepts as serial verbs, serial verb constructions (SVC) and sequence of verbs , which have been widely used in studies on various languages in the world. When applied to research into the Vietnamese language, however, these terms have caused certain confusion. This paper discusses some relevant concepts and terms in order to help clarify such confusion, avoid improper views and accurately distinguish true serial verb constructions from seemingly similar patterns when studying Vietnamese SVCs. After the analysis, Vietnamese equivalents to the afore-mentioned terms are suggested to ensure consistency and better reflect the true nature of our language.